PROGRAM PENGASUHAN POSITIF DAN BINA KELUARGA MUDA DI KOTA SEMARANG - Hastaning Sakti; Diana Rusmawati; Muhammad Zulfa Alfaruqy (Jurnal Abdi Insani, 2023)
This community services aims to develop a positive parenting program and foster young families in Peterongan Village, South Semarang District, Semarang City. The intervention approach is based on family empowerment and positive parenting according to Pancasila. This program is planned for three years. In the first year, we do an assessment of community needs about anti-stunting, assessment of community parenting models, socialization and distribution of positive parenting modules, and socialization and increase nutrition by consuming eggs. The results of the assessment show that the community element requires positive parenting training and fostering young families in order to form an anti-stunting and mentally healthy generation. Based on positive parenting according to Pancasila, parenting is currently dominated by parental openness to children (19.42) followed by affection (16.72), self-esteem (16.39), attachment (16.04), and spirituality (15,97). The positive parenting training module has been distributed to pregnant women and parents who have children under five years as guidance for parenting. In addition, pregnant women and children under five are enthusiastic to consume eggs regularly. In the future, there is a need for mentoring programs for positive parenting groups and the development of related information technology systems.